Daredevil: Indoor Location Using Sound - Constandache, Ionut; Agarwal, Sharad; Tashev, Ivan; Choudhury, Romit Roy (ACM Mobile Computing and Communications Review (MC2R), 2014)
A variety of techniques have been used by prior work on the problem of smartphone location. In this paper, we propose a novel approach using sound source localization (SSL) with microphone arrays to determine where in a room a smartphone is located. In our system called Daredevil, smartphones emit sound at particular times and frequencies, which are received by microphone arrays. Using SSL that we modified for our purposes, we can calculate the angle between the center of each microphone array and the phone, and thereby triangulate the phone’s position. In this early work, we demonstrate the feasibility of our approach and present initial results. Daredevil can locate smartphones in a room with an average precision of 3.19 feet. We identify a number of challenges in realizing the system in large deployments, and we hope this work will benefit researchers who pursue such techniques.